Karakteristik Kondisi Air Minum Menurut Wilayah Perkotaan dan Perdesaan di Indonesia Menggunakan Metode CHAID - Aulia Wanda; Yenni Kurniawati (Departemen Statistika Universitas Negeri Padang, 2024)
Drinking water is the basic needs of society’s basic instead of food, clothing and shelter. The availability and quality of drinking water needs to be considered, both in terms of quantity and suitability which must meet the requirements. Having clean water as drinking water can reduce diseases such as diarrhea, cholera, dysentery, typhus, worms, skin diseases and poisoning. Decent and clean drinking water is protected drinking water, including tap water, public taps, public hydrants, water terminals, rainwater reservoirs, or protected springs and wells, drilled wells/pumps with the closest distance being 10 meters from the location of waste disposal, waste storage and rubbish disposal. Access to drinking water in urban areas is different compared to that in rural areas. To determine the characteristics of drinking water in urban and rural areas, Chi-Square Automatic Interaction Detection (CHAID) analysis is used. This analysis is used on categorical type variables. Before the analysis stage, there is a data mining process to obtain knowledge from the data cluster and handle missing data in the data cluster. Handling of missing data in categorical variables is done by imputation mode. Using CHAID analysis, drinking water characteristics for rural areas with the highest percentage were filtered using cloth and not boiled and the water source was elsewhere. Meanwhile, in urban areas, the highest percentage of households with drinking water characteristics are treated with bleach/chlorine, not filtered using cloth, and not boiled with a water source in their own yard.